Effect of sintering aids on microstructure and properties of textured SiC ceramics prepared in 6 T. Issue 1 (2nd January 2021) - Yang, Zhigang; Yin, Ziqiang; Zhao, Zhijia; Yu, Jianbo; Ren, Zhongming; Yu, Gang; Zhang, Guanglei
ABSTRACT: C-axis textured α-SiC ceramics were prepared by gel-casting in a strong magnetic field of 6 T and subsequent sintering at 1950 °C for 2 h. The effects of sintering aids on the microstructure and properties of textured SiC ceramics were discussed. Results showed that highly textured α-SiC green bodies were obtained by gel-casting in a strong magnetic field of 6 T. The sintering process slightly suppressed the texture development of α-SiC ceramic. The degree of texture in the α-SiC green bodies and sintered bodies both showed a decreasing trend with the increase of sintering aids content. And the increase of the sintering aids content promoted the densification and improved the bending strength of α-SiC ceramics. Besides, the bending strength of textured SiC ceramics showed an anisotropy based on the grain orientation.